Environmental diagnosis of hazardous household wastes and the family health strategy as liaison for implementation of a management program in the South of Brazil - André Preissler Loureiro Chaves; Roni Bitencourt da Silva (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2015)
AbstractDespite the serious threat to public health that it represents, hazardous household waste (HHW) is not perceived as dangerous by a majority of the population. Existing waste management systems contribute to this misperception, by underestimating the importance of these residues. This, in practice, reflects the lack of knowledge of citizens about the risks and about their responsibility. This study aimed to identify the major HHW generated and disposal practices of the population of São Luís District and know the HHW management situation of the municipality of Canoas, Brazil. We conducted a neighborhood survey, identifying the generation and destination of 15 types of HHW. The situation of the management of this waste was obtained through consultations with the City of Canoas, where we observed little effective action to correct mismanagement. With the aim of improving the current administration, this paper proposes the use of the Family Health Strategy as a liaison for implementation of an appropriate hazardous household waste management program. The role of Community Health Workers restates the important potential for the integration of environmental education and preventive action.